A Single Mutation in a Regulatory Protein Produces Evolvable Allosterically Regulated Catalyst of Nonnatural Reaction1. Issue 24 (29th April 2013) - Moroz, Olesia V.; Moroz, Yurii S.; Wu, Yibing; Olsen, Alissa B.; Cheng, Hong; Mack, Korrie L.; McLaughlin, Jaclyn M.; Raymond, Elizabeth A.; Zhezherya, Krystyna; Roder, Heinrich; Korendovych, Ivan V.
<x xml:space="preserve">Abstract</x> It only takes one mutation: A strategically placed single mutation in a non‐enzymatic protein scaffold produced AlleyCat, a small, allosterically regulated catalyst of Kemp elimination. In only seven rounds of directed evolution the enzymatic efficiency of the original 74 amino acid residue catalyst was improved more than 220‐fold to achieve a kcat value higher than that of catalytic antibodies for the same reaction, still preserving allosteric regulation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>